The awareness and implementation of urban green infrastructure planning in Mukalla of Yemen - Bagazi, Omar (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2021)
Green Infrastructure (GI) is a new term that aims to accomplish sustainable development. It is a platform to achieve the balance between environmental preservation and urban development as well as to achieve a set of economic, social, and ecological benefits. However, many countries suffering from a slowdown in GI implementation, especially developing countries. Therefore, this research aims to assess the level of awareness of GI implementation among practitioners in Mukalla city. To achieve the aim of this research, a quantitative research approach was adopted and the questionnaire was designed to contain three main sections. the first section contains a phrase for assessing awareness (knowledge, attitude, and behavior), the second and third sections contain phrases to clarify GI implementation (drivers, barriers, and solutions). The questionnaire was distributed manually to the agencies interested in planning and designing the urban area in Mukalla. The total number of completed questionnaires was 82. Descriptive Statistical and Inferential Statistics tools were used to analyze the data of this study. Regarding objectives 1 and 2, our results show that the level of GI awareness among practitioners in Mukalla city was low at x̄ = 2.87 and the factors gender and education had a significant effect (P-value < 0.05) on their awareness about GI. regrinding objectives 3 and 4 our results show that the main drivers of having GI in Mukalla are enhanced human health and human wellbeing. While the main barriers to GI implementation in Mukalla are financial constraints and lack of experience. Our result also shows that the best strategy to overcome financial constraints is to gain financial support from public sectors, while the best strategy to overcome lack of experience is to training the practitioners themselves. This research will provide the decision-maker with information about what is happening behind the slowdown of GI implementation. It will lead to more effort to raise the level of knowledge among practitioners. Moreover, this study will be a starting point and basis for other researches in the field of GI. In conclusion, we recommend for researchers conduct more scientific studies in the field of GI, especially in developing countries, as they are in urgent need of sustainable solutions to develop their infrastructure.